Different views on law determine the separate representations of legal meanings in information systems - Čyras, Vytautas (Information & Media, 2018)
This paper is concerned with the legal and legal documentation system as well as their interconnectedness. An exploratory research on the operational treatment of legal meaning is presented. The research question is based on how should the legal meaning of a legal act be represented. In our approach, legal meaning is related with to representation; for comparison, see the FRISCO framework and the semiotic tetrahedron. We explain the reasons for the multiple meanings of a legal act and its representation in separate information systems, because various stakeholders view the act differently. The Schweighofer’s eight views/four methods/four syntheses model is presented to reveal different contents. Views are related with representations.